(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2014)
This paper introduces one-leg hybrid methods for solving ordinary differential equations (ODEs) and differential algebraic equations (DAEs). The order of convergence of these methods are determined and compared to the order of convergence of their twin hybrid multistep methods. The G-stability of these methods are studied. Finally, the methods are tested by solving DAEs.